Development of E-Magazine Materials for Disaster Mitigation Outbreak to Increase Preparedness of High School Students - Dwia Arfianti; Rita Retnowati; Muhammad Taufik Awaludin (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2021)
Indonesia is located in the Pacific Ring of Fire, which is often hit by natural disasters. The potential for co-occurrence with other natural disasters can exacerbate human losses and cause chaos. After the occurrence of natural disasters, in addition to causing many casualties and damage to infrastructure, the threat of health risks becomes a serious problem. Especially the emergence of infectious diseases. The number of fatalities indicates that community preparedness and mitigation against disasters are still poor. Disaster mitigation is the knowledge that students must have to have good preparedness behavior. Education related to disasters is usually based on theoretical knowledge so that it becomes less meaningful for students. For this reason, it is necessary to make efforts to increase the value of student preparedness with interesting learning media, one of which is by developing an e-magazine of disease outbreak disaster mitigation materials to improve student preparedness. Based on the results of observations in one high school in Bogor City, it was found that the level of student preparedness was still relatively low at 42%. This study aims to determine the effect of e-magazines on disease outbreak disaster mitigation materials on increasing student preparedness, as well as to determine the effectiveness of e-magazines on disease outbreak disaster mitigation materials. The study was conducted using the Research and development method using the ADDIE model (analyze, design, development, implementation, evaluation). The population in this study were students of class X MIPA with a sample of 30 respondents. The results showed that the e-magazine was able to increase the student's preparedness score to 69.67% which was in the medium category. The effectiveness of learning media can be seen from the responses of students and teachers. The percentage of the average value of student responses is 89.5% with a very effective category. Based on the results of the teacher's response questionnaire, the percentage was 84.17% with a very effective category.